2015
DOI: 10.1016/j.tre.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

How air transport connects the world – A new metric of air connectivity and its evolution between 1990 and 2012

Abstract: SUMMARY ObjectiveScheduled air transport services connect airports throughout the world and thereby enable interaction on a global scale. By doing so, they spur globalization (Hummels, 2007) as well as social and economic development (Lakshmanan, 2011). In order to facilitate integration of regions into global value chains, planners, scholars and policymakers therefore need to understand as to how scheduled air transport services link a region to other markets. For this purpose, connectivity metrics have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 91 publications
(162 reference statements)
2
43
0
Order By: Relevance
“…This result is anticipated by Allroggen et al (2015) who have found connectivity to Asian cities has increased according to their measures over the last two decades. To concentrate on the most important places in this group, Table 4 identifies the eight cities that had at least a 2% share of Australia-Asia passengers in both 2000 and 2013.…”
Section: Identifying Inter-continental Gatewaysmentioning
confidence: 75%
“…This result is anticipated by Allroggen et al (2015) who have found connectivity to Asian cities has increased according to their measures over the last two decades. To concentrate on the most important places in this group, Table 4 identifies the eight cities that had at least a 2% share of Australia-Asia passengers in both 2000 and 2013.…”
Section: Identifying Inter-continental Gatewaysmentioning
confidence: 75%
“…An overview of the models discussed in Burghouwt and Redondi (2013) are shown in Table 1. More recently developed models incorporate the connection quality, frequency and importance of the destination, calibrated on observed passenger behaviour (Allroggen et al, 2015;Seredynski et al, 2014).…”
Section: Connectivity Modelsmentioning
confidence: 99%
“…Appropriate connectivity measures allow policy makers and airports to benchmark the network performance of airports and evaluate policy objectives (Burghouwt and Redondi, 2013). Insights gained from these analyses are also valuable to appraise air transport-related policy measures such as airport infrastructure investments or route subsidies, as well as to identify macro-level trends in airport connectivity in certain regions (Allroggen et al, 2015;Burghouwt and Veldhuis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The RFE was partially validated for the domestic portion, using the empirical observations in DB1B. We compared three test models, specified in Table III, to confirm the effects of the additional constraints (3) and (4), and the route attractiveness function (14), with respect to the model performance. M1 is the basic model and only includes the segment traffic balancing constraint (2) with the exponential decay function alone (without the route capacity), while M2 includes the route attractiveness function (14).…”
Section: Model Validation With Sensitivity Tests For the Decay Coeffimentioning
confidence: 99%